Teaching Speaking Recount Text by Using Facebook about Students Activities - Dewi Sri Wahyuni (PGRI Provinsi Jawa Timur, 2022)
The purpose of the research was to describe the implementation of the teaching speaking by describing picture series on the facebook about students activities and to find out the students’ responses in teaching speaking by describing picture series on the facebook about students activities. The subjects of this research were the teacher and the students at the tenth grade. This research was descriptive qualitative with the data collected from field note observation, check list observation and questionnaire. The findings of teaching speaking by describing picture series on the facebook about students activities were: The first meeting, the teacher give warming up, explained recount text, asked student to describe pictures that already prepared by teacher with simple word and a few sentence. The second meeting, the students practice speaking using picture series that already uploaded on the facebook and they practice one by one in front of class. In this teaching process show the percentage answer YES 60% and NO 40%. It means the students had interested in learning teaching speaking by describing picture series on the facebook